A LES-based Eulerian–Lagrangian approach to predict the dynamics of bubble plumes. (January 2016) - Fraga, Bruño; Stoesser, Thorsten; Lai, Chris C.K.; Socolofsky, Scott A.
Highlights: A new Lagrangian Particle Tracking algorithm for LES of bubble plumes is presented. Delta functions are applied for the first time to the knowledge of the authors to this kind of problem. A new mapping approach based on the use of the bubble to mesh size ratio is suggested. We successfully validate the time-averaged velocities and second-order turbulence statistics. Slip velocity, interfacial forces and confinement effect are also analysed. Abstract: An approach for Eulerian–Lagrangian large-eddy simulation of bubble plume dynamics is presented and its performance evaluated. The main numerical novelties consist in defining the gas-liquid coupling based on the bubble size to mesh resolution ratio ( Dp / Δx ) and the interpolation between Eulerian and Lagrangian frameworks through the use of delta functions. The model's performance is thoroughly validated for a bubble plume in a cubic tank in initially quiescent water using experimental data obtained from high-resolution ADV and PIV measurements. The predicted time-averaged velocities and second-order statistics show good agreement with the measurements, including the reproduction of the anisotropic nature of the plume's turbulence. Further, the predicted Eulerian and Lagrangian velocity fields, second-order turbulence statistics and interfacial gas-liquid forces are quantified and discussed as well as the visualization of the time-averaged primary and secondary flow structure in the tank.